2014
DOI: 10.1111/pim.12151
|View full text |Cite
|
Sign up to set email alerts
|

The production and comparative evaluation of native and recombinant antigens for the fast serodiagnosis of cystic echinococcosis with dot immunogold filtration assay

Abstract: Clinical diagnosis and post-surgery assessment of cystic echinococcosis depend on laboratory serodiagnosis and ultrasound examinations. This study aims to produce the recombinant antigen (rAgB) and compare its diagnostic effect with natural antigens (crude fluid antigen, protoscolex antigen). After rAgB, crude fluid antigen, protoscolex antigen were produced, and the diagnostic accuracy was evaluated with dot immunogold filtration assay (DIGFA) by the sera from the following groups: surgically confirmed cystic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
(28 reference statements)
0
11
1
Order By: Relevance
“…Similarly, Tamer and colleagues [ 14 ], evaluating the performances of the VIRapid test, reported a better Se (96.8%) and same Sp (96% if sera from patients with other parasitoses were excluded – 87.5% if included) compared to our results, but they did not provide data on cyst characteristics; all CE patients included in their cohort where surgically confirmed, suggesting that predominantly active CE stages were included. Finally, Chen and colleagues [ 11 ], using sera from hospital cases, reported that the use of recombinant antigens in the DIGFA test might improve the specificity of the test, but at the expense of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tamer and colleagues [ 14 ], evaluating the performances of the VIRapid test, reported a better Se (96.8%) and same Sp (96% if sera from patients with other parasitoses were excluded – 87.5% if included) compared to our results, but they did not provide data on cyst characteristics; all CE patients included in their cohort where surgically confirmed, suggesting that predominantly active CE stages were included. Finally, Chen and colleagues [ 11 ], using sera from hospital cases, reported that the use of recombinant antigens in the DIGFA test might improve the specificity of the test, but at the expense of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, antibodies from patients with other parasitic diseases including onchocerciasis, schistosomiasis, and toxocariasis have given rise to false positive reactions when tested against EgAgB [ 11 ]. It is worth mentioning the efforts of several authors to test new affordable and easy to use serological techniques instead of ELISA or the IB tests, making those immunoassays stand out based on particles such as DIGFA (dot immunogold filtration assay [ 43 , 44 ]; Table 2 ).…”
Section: Antigens Derived From Hydatid Fluidmentioning
confidence: 99%
“…The most frequently used crude extract of E. granulosus for the serodiagnosis of CE has been the somatic extract of protoscoleces (EgPpsSom). This extract has a Se ranging from 69.4% to 96.9% [ 11 , 16 , 43 , 44 , 52 54 ]. When compared with HF, the EgPpsSom performs worse.…”
Section: Antigens Derived From Hydatid Fluidmentioning
confidence: 99%
“…Several recombinant antigens and synthetic peptides have been used for CE serodiagnosis in humans. [9][10][11][12][15][16][17][18] A highly antigenic protein, named EPC1, was characterized and isolated from a protoscolex (larval) stage and is encoded by the EPC1 gene. 13,17 Our previous study was aimed to assess the sequence of EPC1 isolated from different intermediate hosts of E. granulosus, including sheep (G1 strain) and camel (G6 strain).…”
Section: Discussionmentioning
confidence: 99%